Macroeconomic Impacts of Gender Inequality and Informality in India - Khera, Purva (IMF Working Papers; Working Paper, 2016)
This paper examines the macroeconomic interaction between informality and gender inequality in the labor market. A dynamic stochastic general equilibrium model is built to study the impact of gender-targeted policies on female labor force participation, female formal employment, gender wage gap, as well as on aggregate economic outcomes. The model is estimated using Bayesian techniques and Indian data. Although these policies are found to increase female labor force participation and output, lack of sufficient formal job creation due to labor market rigidities leads to an increase in unemployment and informality, and further widens gender gaps in formal employment and wages. Simultaneously implementing such policies with formal job creating policies helps remove these adverse impacts while also leading to significantly larger gains in output.